Illicit trade and cultural heritage in South Africa: investigating the policy environment and opportunities for digitisation - Mabe, Thandiwe Sibulele (Library and Information Studies Centre (LISC), 2025)
This dissertation addresses research questions aimed at understanding and addressing the issue of illicit trafficking in cultural heritage assets in South Africa. The specific research questions guiding this study are as follows: ● What is the state of illicit trafficking in cultural heritage assets in South Africa? ● To what extent does the South African policy environment respond to the illicit trade of cultural heritage assets? ● To what extent can digital curation serve as a solution to the illicit trade of cultural. heritage assets in South Africa? A qualitative methodology was employed to answer these questions using semi- structured interviews. The study explored cultural heritage management in South Africa and the effectiveness of cultural heritage policy in addressing the illicit trade in cultural heritage. It investigated the challenges and opportunities associated with digitising cultural heritage in South Africa. A sample of six people from the population of specialists in the cultural heritage sector participated in the study. The findings of this study shed light on the complex nature of illicit trafficking in cultural heritage within South Africa and the challenges in implementing effective policies for preserving and managing cultural heritage. Also, it highlights the role of digital curation as a potential solution in the fight against the illicit trade of cultural heritage. As a result of these findings, several recommendations are proposed to address the identified issues. These include increased funding for projects within the cultural heritage field with a specific focus on devising effective strategies against the illicit trafficking of cultural heritage; establishing mechanisms for the ongoing review and evaluation of policies related to cultural heritage and technology by governments and cultural heritage organisations; giving attention to cultural policy to establish effective guidelines and principles for the return of cultural heritage assets; and integrating museum collection records management systems with investigative agencies' databases for cross-referencing analysis to comprehensively combat the illegal movement of cultural heritage items.